Adjusting Porosity and Pore Radius of Electrodeposited ZnO Photoanodes. Issue 9 (1st January 2019) - Nguyen, Thi Hai Quyen; Ruess, Raffael; Schlettwein, Derck
Abstract : The optimization of the porosity and pore radius of ZnO for the application in dye-sensitized solar cells is essential to enhance the cell performance. Porous ZnO films were fabricated by electrodeposition in the presence of eosin Y or in combination with eosin B which was used as a structure directing agent (SDA) for the first time. The influence of the deposition time and the SDA concentration on film porosity and pore radius was characterized by a combined electrochemical and atomic absorption spectroscopy analysis, and confirmed by gas sorption, optical spectroscopy and scanning electron microscopy. The combination of eosin Y with eosin B as SDA results in porous ZnO films with larger pore radius compared to the films prepared with eosin Y only. The larger pores showed a significantly decreased diffusion impedance leading to an increased photocurrent less hindered by mass transport. Successful application of these new ZnO films in dye-sensitized solar cells confirmed improved pathways for large complex ions as redox shuttles through the ZnO pore structure.